Times Square style : graphics from the Great White Way / by Vicki Gold Levi and Steven Heller. - Levi, Vicki Gold (Princeton Architectural, 2004)
This is a collection of graphic ephemera from Times Square. It is a trove of lost, forgotten, and arcane promotions, signage, flyers, programs, posters, records, napkins, advertisements, and billboards.